Drug-coated balloon versus drug-eluting stent following orbital atherectomy for calcified coronary artery: one-year outcomes of a retrospective cohort study. (14th October 2021) - Mitsui, K; Lee, T; Miyazaki, R; Hara, N; Nagamine, S; Nakamura, T; Terui, M; Okata, S; Nagase, M; Nitta, G; Watanabe, K; Kaneko, M; et al.
Abstract: Background: Percutaneous coronary intervention (PCI) for calcified coronary artery remains challenging in the drug-eluting stent (DES) era. The effectiveness of drug-coated balloons (DCBs) and orbital atherectomy system (OAS) is unknown. Methods: In this retrospective, single-center study, we compared the use of DCBs with second- and third-generation DESs following orbital atherectomy (OA) for calcified de novo coronary lesions. All patients underwent PCI with intravascular imaging. The primary endpoint was major cardiac event, that was a composite of cardiac death, death for unknown cause, non-fatal myocardial infarction, or target lesion revascularization at 1 year. Results: Between June 2018 and December 2019, 107 patients with coronary lesions were enrolled in this study and divided into two groups: 23 patients in DCB group and 84 patients in DES group. The post-procedure segment percentage diameter stenosis was 23.1% (interquartile range [IQR], 17.7 to 32.5) with DCB versus 14.4% (IQR, 10.0 to 21.2) with DES (P<0.001). Overall adverse event rate for PCI procedure was low: one dissection with DES group, no persistent slow/no-flow, and no perforation with both group. The primary endpoint was not significantly different between 2 groups [DES: 6.0% (5/84), DCB: 0.0% (0/23), log-rank P=0.24]. Conclusions: In calcified coronary artery disease, using DCB following OA is as safe and effective as using DES following OA with respect to 1-year clinical outcomes. FUNDunding Acknowledgement: Type of funding sources: None.